A Pivotal Role for Interleukin-27 in CD8+ T Cell Functions and Generation of Cytotoxic T Lymphocytes. (29th April 2010) - Morishima, Noriko; Mizoguchi, Izuru; Okumura, Masae; Chiba, Yukino; Xu, Mingli; Shimizu, Motomu; Matsui, Masanori; Mizuguchi, Junichiro; Yoshimoto, Takayuki
Abstract : Cytotoxic T lymphocytes (CTLs) play a critical role in the control of various cancers and infections, and therefore the molecular mechanisms of CTL generation are a critical issue in designing antitumor immunotherapy and vaccines which augment the development of functional and long-lasting memory CTLs. Interleukin (IL)-27, a member of the IL-6/IL-12 heterodimeric cytokine family, acts on naive CD 4 + T cells and plays pivotal roles as a proinflammatory cytokine to promote the early initiation of type-1 helper differentiation and also as an antiinflammatory cytokine to limit the T cell hyperactivity and production of pro-inflammatory cytokines. Recent studies revealed that IL-27 plays an important role in CD 8 + T cells as well. Therefore, this article reviews current understanding of the role of IL-27 in CD 8 + T cell functions and generation of CTLs.